Newlyweds’ Optimistic Forecasts of their Marriage: For Better or For Worse? - Lavner, Justin A. (2013)
Newlywed spouses routinely hope and believe that their relationships will thrive, but theoretical accounts differ on whether optimistic projections such as believing that one’s marriage will improve are sources of strength, random forecasting errors, or self-protective mechanisms. To test these opposing perspectives, we asked 502 newlywed spouses in 251 marriages to predict how their overall feelings about their relationships would change over the following four years, and we then compared these reports to their prospective marital satisfaction trajectories. Nearly all spouses predicted their marital satisfaction would remain stable or improve over the following four years. Marital satisfaction declined on average despite this high overall level of optimism. Wives with the most optimistic forecasts showed the steepest declines in marital satisfaction. These wives also had lower self-esteem and higher levels of stress and physical aggression toward their partners initially. Thus, believing that one’s marriage will improve does not make it so and instead may paradoxically mask risky relationships among women. These findings may be important in helping to understand low rates of premarital counseling utilization by showing that nearly all couples overestimate the durability of their existing satisfied feelings at the start of their marriage. Future research is needed to understand the psychological processes allowing couples to commit to and stay in risky relationships.